Presence of UV filters in surface water and the effects of phenylbenzimidazole sulfonic acid on rainbow trout (Oncorhynchus mykiss) following a chronic toxicity test - Grabicova, Katerina; Fedorova, Ganna; Burkina, Viktoriia; Steinbach, Christoph; Schmidt-Posthaus, Heike; Zlabek, Vladimir; Kocour Kroupova, Hana; Grabic, Roman; Randak, Tomas (Ecotoxicology and environmental safety, 2013)
UV filters belong to a group of compounds that are used by humans and are present in municipal waste-waters, effluents from sewage treatment plants and surface waters. Current information regarding UV filters and their effects on fish is limited. In this study, the occurrence of three commonly used UV filters - 2-phenylbenzimidazole-5-sulfonic acid (PBSA), 2-hydroxy-4-methoxybenzophenone (benzophenone-3, BP-3) and 5-benzoyl-4-hydroxy-2-methoxy-benzenesulfonic acid (benzophenone-4, BP-4) - in South Bohemia (Czech Republic) surface waters is presented. PBSA concentrations (up to 13μgL(-1)) were significantly greater than BP-3 or BP-4 concentrations (up to 620 and 390ngL(-1), respectively). On the basis of these results, PBSA was selected for use in a toxicity test utilizing the common model organism rainbow trout (Oncorhynchus mykiss). Fish were exposed to three concentrations of PBSA (1, 10 and 1000µgL(-1)) for 21 and 42 days. The PBSA concentrations in the fish plasma, liver and kidneys were elevated after 21 and 42 days of exposure. PBSA increased activity of certain P450 cytochromes. Exposure to PBSA also changed various biochemical parameters and enzyme activities in the fish plasma. However, no pathological changes were obvious in the liver or gonads.
Keywords: benzophenone-4; testy chronické toxicity; Cytochromes; oxidační stres; 4MBC; Sulfonic Acids; octocrylene; benzophenone-3; játra; přípravky chránící proti slunci; OC; Česká republika; voda; Oxidative Stress; cytochromy; Oncorhynchus mykiss; BP-4; Czech Republic; 2-Phenylbenzimidazole-5-sulfonic acid; Chronic toxicity test; 4-methyl-benzylidene camphor; Surface water; chemické látky znečišťující vodu; 2-phenylbenzimidazole-5-sulfonic acid; 2-ethyl-hexyl-4-trimethoxycinnamate; benzimidazoly; Water Pollutants, Chemical; PBSA; Sunscreening Agents; Toxicity Tests, Chronic; Water; pharmaceuticals and personal care products; Benzimidazoles; Animals; PPCPs; Liver; zvířata; BP-3; Rainbow trout; kyseliny sulfonové; UV filters; EHMC